Open Versus Closed Negative Pressure Wound Therapy For Contaminated and Dirty Surgical Wounds: A Quasi-Experimental Study - Hameed, Saqib; Hanif, Mubashir; Salamat, Zaki Hussain; Ilyas, Sohail; Farooq, Omar; Rehman, Shafqat (Pakistan Armed Forces Medical Journal, 2024)
Objectives: To determine the efficacy of open versus closed negative pressure wound therapy for contaminated and dirty surgical wounds in terms of time duration to full wound healing. Study Design: Quasi-experimental study. Place and Duration of Study: Department of General Surgery, Combined Military Hospital, Quetta Pakistan, from Oct 2021 to Apr 2022. Methodology: A total of 96 patients with surgical wounds requiring repair were included for study. All patients underwent their respective surgery followed by grouping. Patients in Group-A received closed negative pressure wound therapy while those in Group-B received open negative pressure wound therapy. All patients were followed up till complete healing of the wound or till the occurrence of complications. Results: Our study sample had a mean age of 44.16±12.66 years, with a slight female preponderance of 51(53.1%) participants. The mean total healing time for closed negative pressure wound therapy was 17.35±6.95 days, while it was 42.00±16.21 days with open negative pressure wound therapy, (p<0.001). There was no difference between the two groups with regards to the total complication rate, or the occurrence of individual complications, (p>0.05). Conclusion: Closed negative pressure wound therapy results in faster wound healing, with a similar complication rate as open negative pressure wound therapy.